Effectiveness of Inquiry Model with Scientific Approach and Experimental Methods in Science Learning for Elementary School - Erny Paembonan; Nurdin Arsyad; Udan Kusmawan (PT ARRUS Intelektual Indonesia, 2023)
The purpose of this research is to analyze effectivity of inquiry model with scientific approach and experimental methods to collecting data in learning science for elementary school students. The approach used is a quantitative pre-experimental design that uses one experimental class. Data were collected using tests at the beginning and the end of the treatment, observations during learning and questionnaires at the end of the treatment which were then analyzed descriptively and inferentially. Based on the analysis of learning outcomes data obtained an increase in scores from pretest to posttest in the high category with a gain value of 0.70339. In addition, based on the t test, the sig. (2-tailed) = 0.000 <0.05 which shows that the average posttest meets the KKM score and 92% of students fulfill the classical learning mastery. Based on the observations obtained, 85.3% of students' activity was positive when learning and 84.16% of students gave positive responses regarding learning. Therefore, it can be concluded that the inquiry model with scientific approach and the experimental method to collecting data is effective in elementary school science learning